2015
DOI: 10.1177/0363546515572143
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trochlear Dysplasia on Patellofemoral Biomechanics

Abstract: Investigating the relationship between the shape of the trochlea and patellofemoral biomechanics can provide insight into the short-term effects (maltracking, increased pressures, and instability) and long-term effects (osteoarthritis) of different types of trochlear dysplasia. Furthermore, this investigation provides an empirical explanation for better treatment outcomes of trochleoplasty for Dejour types B and D dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(64 citation statements)
references
References 28 publications
5
58
1
Order By: Relevance
“…Computational reconstruction of in vivo function studies have indicated that, for subjects with patellar instability, the level of trochlear dysplasia and the lateral position of the tibial tuberosity are correlated with lateral patellar tracking, particularly at low flexion angles [37, 38]. An in vitro simulation of knee function study also indicated that trochlear dysplasia is associated with increased contact pressures [39]. Without accounting for these anatomical factors, the simulated in vitro function does not produce lateral tracking or elevated contact pressures to the degree noted for symptomatic knees.…”
Section: Summary Of Results and Limitationsmentioning
confidence: 99%
“…Computational reconstruction of in vivo function studies have indicated that, for subjects with patellar instability, the level of trochlear dysplasia and the lateral position of the tibial tuberosity are correlated with lateral patellar tracking, particularly at low flexion angles [37, 38]. An in vitro simulation of knee function study also indicated that trochlear dysplasia is associated with increased contact pressures [39]. Without accounting for these anatomical factors, the simulated in vitro function does not produce lateral tracking or elevated contact pressures to the degree noted for symptomatic knees.…”
Section: Summary Of Results and Limitationsmentioning
confidence: 99%
“…In the axial plane, a shallower/wider trochlea and a patella that is more laterally displaced or tilted are associated with more severe patellofemoral OA features 12 , and trochlear morphology is associated with patellofemoral alignment 13, 14 . Theoretically, trochlear dysplasia may cause patellar instability and result in malalignment and/or aberrant movement patterns at the patellofemoral joint.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, trochlear dysplasia may cause patellar instability and result in malalignment and/or aberrant movement patterns at the patellofemoral joint. Patellofemoral malalignment reduces contact area which increases joint stress during activities of daily living 13, 15 , potentially leading to OA. To date, our understanding is limited as to what extent patellofemoral alignment and trochlear morphology contribute - either independently or together - to the onset or progression of patellofemoral OA 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…20 Increased patellar lateral tilt, lateral tracking and external rotation were found in the dysplastic models compared with the normal joint, especially for type D dysplasia in open-chain activity simulation. Also, an increased patellofemoral pressure and a reduced patellofemoral contact area were reported in trochlear dysplasia, more pronounced in B and D types.…”
Section: Biomechanics Of Dysplasiamentioning
confidence: 92%